2019
DOI: 10.1007/jhep08(2019)039
|View full text |Cite
|
Sign up to set email alerts
|

Top-quark pair hadroproduction in association with a heavy boson at NLO+NNLL including EW corrections

Abstract: This work studies the associated production of a top-quark pair with a W , Z, or Higgs boson at the LHC. Predictions for the total cross sections as well as for several differential distributions of the massive particles in the final state are provided. These predictions, valid for the LHC operating at 13 TeV, include without any approximation all the NLO electroweak and QCD contributions of O(α i s α j+1 ) with i + j = 2, 3. In addition, the predictions presented here improve upon the NLO QCD results by addin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 107 publications
4
112
1
Order By: Relevance
“…Following the notation already used in Refs. [42,[72][73][74][75][76][77][78], with complete-NLO predictions we denote all the one-loop and real emission corrections of QCD and EW origin. To this purpose we calculate all the O(α m s α n+2 ) contributions with m, n > 0 and m + n = 2, 3 to pp → ν e JJJ , (2.2) where J is any particle that may potentially enter in a fully-democratic jet, i.e., a jet that is obtained by clustering quarks (including b-quarks), gluons, photons and leptons.…”
Section: Structure Of the Calculation: Underlying Resonances And Notamentioning
confidence: 99%
“…Following the notation already used in Refs. [42,[72][73][74][75][76][77][78], with complete-NLO predictions we denote all the one-loop and real emission corrections of QCD and EW origin. To this purpose we calculate all the O(α m s α n+2 ) contributions with m, n > 0 and m + n = 2, 3 to pp → ν e JJJ , (2.2) where J is any particle that may potentially enter in a fully-democratic jet, i.e., a jet that is obtained by clustering quarks (including b-quarks), gluons, photons and leptons.…”
Section: Structure Of the Calculation: Underlying Resonances And Notamentioning
confidence: 99%
“…Expanding in powers of α s and α and following the notation already used in refs. [17][18][19][20][21][22][23][24][25], the different contributions to any differential or inclusive cross section Σ can be denoted as:…”
Section: Calculation Setupmentioning
confidence: 99%
“…quark physics, such as, e.g., ttW and tttt for which the two approximations are different and lead to sizeable numerical differences due to contributions that are formally suppressed w.r.t. the NLO EW in the (α s /α) power counting [23,24,26,27].…”
Section: Jhep08(2020)082mentioning
confidence: 99%
“…This large contribution is due to the opening of t W → t W scattering diagrams, which are also studied in detail in [6] within a BSM context. The complete-NLO calculation has been matched a e-mail: rikkert.frederix@thep.lu.se b e-mail: ioannis.tsinikos@thep.lu.se (corresponding author) to soft (threshold) gluon resummation, resulting in the mostaccurate predictions for the tt W production at the LHC to date [7,8]. Both these works have shown that tt W , in contrast to tt Z and tt H, does not become less sensitive to the scale choices even when including the resummation at NNLL accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Since they do not contribute at LO they are not considered in the resummation frameworks of Refs. [7,8]. Incidentally, since the gg channels only open at NNLO accuracy there is a large tt asymmetry of ∼3% in tt W production [7,9,10].…”
Section: Introductionmentioning
confidence: 99%